HMGA1a recognition candidate DNA sequences in humans. - Takayuki Manabe; Taiichi Katayama; Masaya Tohyama (PLoS ONE, 2009)
High mobility group protein A1a (HMGA1a) acts as an architectural transcription factor and influences a diverse array of normal biological processes. It binds AT-rich sequences, and previous reports have demonstrated HMGA1a binding to the authentic promoters of various genes. However, the precise sequences that HMGA1a binds to remain to be clarified. Therefore, in this study, we searched for the sequences with the highest affinity for human HMGA1a using an existing SELEX method, and then compared the identified sequences with known human promoter sequences. Based on our results, we propose the sequences "-(G/A)-G-(A/T)-(A/T)-A-T-T-T-" as HMGA1a-binding candidate sequences. Furthermore, these candidate sequences bound native human HMGA1a from SK-N-SH cells. When candidate sequences were analyzed by performing FASTAs against all known human promoter sequences, 500-900 sequences were hit by each one. Some of the extracted genes have already been proven or suggested as HMGA1a-binding promoters. The candidate sequences presented here represent important information for research into the various roles of HMGA1a, including cell differentiation, death, growth, proliferation, and the pathogenesis of cancer.